VEGF-targeting drugs for the treatment of retinal neovascularization in diabetic retinopathy - Alessandro Arrigo; Emanuela Aragona; Francesco Bandello (Annals of Medicine, 2022)
Diabetic retinopathy (DR) is the most common microangiopathic complication of diabetes mellitus, representing a major cause of visual impairment in developed countries. Proliferative DR (PDR) represents the last stage of this extremely complex retinal disease, characterized by the development of neovascularization induced by the abnormal production and release of vascular endothelial growth factor (VEGF). The term VEGF includes different isoforms; VEGF-A represents one of the most important pathogenic factors of DR. Anti-VEGF intravitreal therapies radically changed the outcome of DR, due to combined anti-angiogenic and anti-edematous activities. Nowadays, several anti-VEGF molecules exist, characterized by different pharmacological features and duration. With respect to PDR, although anti-VEGF treatments represented a fundamental step forward in the management of this dramatic complication, a big debate is present in the literature regarding the role of anti-VEGF as substitute of panretinal photocoagulation or if these two approaches may be used in combination. In the present review, we provided an update on VEGF isoforms and their role in DR pathogenesis, on current anti-VEGF molecules and emerging new drugs, and on the current management strategies of PDR. There is an overall agreement regarding the relative advantage provided by anti-VEGF, especially looking at the management of PDR patients requiring vitrectomy, with respect to laser. Based on the current data, laser approaches might be avoided when a perfectly planned anti-VEGF therapeutic strategy can be adopted. Conversely, laser treatment may have a role for those patients unable to guarantee enough compliance to anti-VEGF injections.Key messagesVEGF increased production, stimulated by retinal hypoperfusion and ischaemia, is a major pathogenic factor of neovascular complication onset in diabetic retinopathy and of DR stages progression.Nowadays, several anti-VEGF molecules are available in clinical practice and other molecules are currently under investigation. Each anti-VEGF molecule is characterized by different targets and may interact with multiple biochemical pathways within the eye.All the data agreed in considering anti-VEGF molecules as a first line choice for the management of diabetic retinopathy. Laser treatments may have a role in selected advanced cases and for those patients unable to guarantee enough compliance to intravitreal treatments schemes.